2012
DOI: 10.1016/j.oraloncology.2012.03.025
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of head and neck cancer quality of life assessment instruments

Abstract: Summary Although quality of life (QOL) is an important treatment outcome in head and neck cancer (HNC), cross-study comparisons have been hampered by the heterogeneity of measures used and the fact that reviews of HNC QOL instruments have not been comprehensive to date. We performed a systematic review of the published literature on HNC QOL instruments from 1990–2010, categorized, and reviewed the properties of the instruments using international guidelines as reference. Of the 2766 articles retrieved, 710 met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(131 citation statements)
references
References 101 publications
0
129
0
2
Order By: Relevance
“…The selected instruments have been taken from different groups, namely the FACT-Head and Neck is a site-specific instrument, and the OHIP-14 is a symptom-specific instrument [8]. It was hypothesised that using instruments from differing paradigms would produce meaningful results.…”
Section: Comparison Of Quality Of Life Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected instruments have been taken from different groups, namely the FACT-Head and Neck is a site-specific instrument, and the OHIP-14 is a symptom-specific instrument [8]. It was hypothesised that using instruments from differing paradigms would produce meaningful results.…”
Section: Comparison Of Quality Of Life Instrumentsmentioning
confidence: 99%
“…In the case of head and neck cancer treated with RT, there can be significant effects on aesthetics, speech, eating and pain, as well as general effects on emotional state, social state and a general functional level [7]. There are numerous quality of life instruments available for the clinician or researcher to use, with a recent review finding 57 separate head and neck specific instruments published [8]. Quality of life instruments attempt to measure the human experience in order to produce a meaningful, thorough and comparable quantity that can be used to ascertain treatment effectiveness beyond the purely biological.…”
Section: Introductionmentioning
confidence: 99%
“…A large prospective study showed that depressed patients have a higher risk of postoperative complications and worse survival [12,21]. Although several tools, such as the Geriatric Depression Scale, have been developed most studies have employed the psychological domain of different quality of life tests [22]. Beyond clinical relevance, depression has several social implications; thus psychological status is usually evaluated in conjunction with available social support.…”
mentioning
confidence: 99%
“…The most commonly used HR-QoL questionnaire to date in studies of patients with HNC [181] is the disease-specific European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-head and neck 35 [182,183], the University of Washington Quality of Life Questionnaire [184], and the Functional Assessment of Cancer Therapy Head and Neck Cancer Questionnaire [185]. These questionnaires address emotional, social, and physical well-being, in addition to disease-specific symptoms such as pain, difficulty swallowing, nausea and fatigue.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%